INVESTIGATION OF THE PROCESS OF FORMATION OF JOINT LINES - СІМОНЧУК, Є. П.; СОКОЛЬСЬКИЙ, О. Л. (Technologies and Engineering, 2022)
Purpose The purpose of the research is to analyze the criteria for the formation of joint lines and minimize their formation by selecting such parameters of the casting mode as the temperature of the mold and the temperature of the melt. Method. To predict the formation of joint lines during injection molding of polymers, a computer calculation model was developed and the range of melt temperatures and shapes at which the joint line for the presented part will be absent was determined. It is proposed to take the meeting angle of the fronts of melt flows as one of the criteria for the formation of fusion lines, and the temperature of such fronts as another criterion. As an example of a part obtained by the method of injection molding, a product in the form of a blade, which is used for strength tests, was chosen. Polyvinyl chloride composition was chosen as the recyclable material. The results. To analyze the dependence of the joint line on the temperature of the mold, numerical studies of such parameters as the angle of the meeting of the flow fronts and the temperature of the flow fronts at certain mold temperatures were analyzed. The influence of the melt temperature on the degree of defect formation of the joint line type has been confirmed. Correctly selected mold and melt temperature for a polymer part formed by the injection molding method helps to eliminate the defect. The joint angle takes on a minimum value at a melt temperature of 210 ºC and a mold temperature of 55–65 ºC. The rise in temperature at the junction line is directly proportional to the rise in melt temperature. There is no melting line at a melt temperature of 185 ºC and below. Scientific novelty. A mathematical model of the non-isothermal flow of laminar flows of a non-Newtonian fluid was created, which describes the process of filling the mold during injection molding. The influence of the melt temperature on the parameters of the joint line has been confirmed. The optimal temperature of the melt to eliminate the fusion line is 180–185 ºC, and the temperature of the mold is 80 ºC. Practical significance. Numerical modeling of the process of formation of joint lines allows you to choose the temperature of the mold and melt, due to which the defect of the finished part will be minimized.